Dengue fefer and mixed abortion among pregnant women: findgs of a comparative cross-sectional study (Journal of Preventive and Social Medicine, 2024)
Background: Dengue situation in Bangladesh has escalated over the last few years causing significant mortality and morbidity. Pregnant women are highly vulnerable to dengue infection leading to various grave complications for both mother and foetus including missed abortion. Despite the severity of this condition, few studies have explored the association of dengue fever with missed abortion in Bangladesh. This study aimed to investigate the association between missed abortion and dengue fever. Methods: This comparative cross-sectional study enrolled 35 pregnant women having the history of missed abortion during the gestational age of less than 22 weeks and 35 pregnant women continuing their pregnancy with gestational age of more than 22 weeks receiving ante natal care. Both groups were selected conveniently. The study was conducted in a private facility from February to October, 2023. Data were collected from medical record review and analyzed with appropriate descriptive and analytical statistics. Cases of missed abortion attributed to dengue infection were compared with pregnant women receiving routine antenatal care if their pregnancies continued beyond 22 weeks’ gestation. Other predictive factors for missed abortion were also examined. Results: Dengue infection was detected among 14 (40%) of pregnant women with missed abortion in comparison to 3 (8.6%) pregnant women without missed abortion. Significant (p